Patients Factors and Medication Use Practices Affecting Blood Pressure Control Among Hypertensive Patients Attending a Secondary Health Facility in Ilorin, North Central Nigeria - Abdulganiyu Giwa; Muslim Olakunle Jamiu; Halima Bukola Giwa; Iyabode Fatima Abdulazeez (Tehran University of Medical Sciences, 2021)
Background: The increase in the prevalence and economic burden of hypertension has been attributable to the poor knowledge of disease management and practices. The proper practices would enhance adequate control of blood pressure. This study aimed to determine patients' characteristics and medication use practices that influence their blood pressure control. Methods: The study was conducted on 202 hypertensive patients attending a Civil Service Hospital, Ilorin, Nigeria. A validated interviewer-administered questionnaire was used for patients' data collection. The collected data were analyzed in SPSS v. 20. Descriptive statistics were used to analyze numerical and categorical variables, and the results are presented in text, percentages, and charts. The Chi-square and logistic regression tests were used as inferential analysis to determine the relationship between categorical variables. P values less than 0.05 were considered significant. Results: The Mean±SD age of the patients was 59.1±13 years, with the highest frequency of hypertension occurring among patients aged 46-60 years (44.6%). Women were more affected (120; 69.4%) than men (82; 40.6%). The majority of the patients (132; 65.3%) were low- to moderate-income earners. Educational status, frequency of missed doses, and presence of comorbidity significantly influenced blood pressure control (P= 0.017, P= 0.039, and P= 0.019, respectively). Knowledge of the timely use of drugs and regular clinic visits significantly affected blood pressure control, too (P=0.014, and P=0.043, respectively). The blood pressure control among patients was fair despite the poor level of medication use knowledge/practices. Conclusion: Blood pressure control is influenced by educational status and the presence of comorbid conditions. Timely medication use and regular clinic visits were strong predictors of blood pressure control. Multiple drug use was the most common hindrance to the timely use of medication. Background: The increase in the prevalence and economic burden of hypertension has been attributable to the poor knowledge of disease management and practices. The proper practices would enhance adequate control of blood pressure. This study aimed to determine patients' characteristics and medication use practices that influence their blood pressure control. Methods: The study was conducted on 202 hypertensive patients attending a Civil Service Hospital, Ilorin, Nigeria. A validated interviewer-administered questionnaire was used for patients' data collection. The collected data were analyzed in SPSS v. 20. Descriptive statistics were used to analyze numerical and categorical variables, and the results are presented in text, percentages, and charts. The Chi-square and logistic regression tests were used as inferential analysis to determine the relationship between categorical variables. P values less than 0.05 were considered significant. Results: The Mean±SD age of the patients was 59.1±13 years, with the highest frequency of hypertension occurring among patients aged 46-60 years (44.6%). Women were more affected (120; 69.4%) than men (82; 40.6%). The majority of the patients (132; 65.3%) were low- to moderate income earners. Educational status, frequency of missed doses, and presence of comorbidity significantly influenced blood pressure control (P= 0.017, P= 0.039, and P= 0.019, respectively). Knowledge of the timely use of drugs and regular clinic visits significantly affected blood pressure control, too (P=0.014, and P=0.043, respectively). The blood pressure control among patients was fair despite the poor level of medication use knowledge/practices. Conclusion: Blood pressure control is influenced by educational status and the presence of comorbid conditions. Timely medication use and regular clinic visits were strong predictors of blood pressure control. Multiple drug use was the most common hindrance to the timely use of medication.